Gut-lung axis, probiotics, and prebiotics: insights on dysbiosis, mechanism, and prevention of lung cancer - Deepika,; Alsharari, Zayed D.; Ahmad, Md Faruque; Singh, Jagphool; Yadav, Mohini; Kumari, Anita; Kumar, Anil; Matthews, Karl R.; Aluko, Rotimi E.; Raposo, António; Albaridi, Najla A.; Mozaffar, Boshra; et al. (Frontiers in Nutrition, 2025)
Background/objectivesScience continues to unravel the intricacies of the human body that affect health and well-being. The human gastrointestinal tract is inhabited by microbiota responsible for various bodily functions and reactions. This review provides an overview of lung-related diseases and the role of the gut-lung axis (GLA) related to lung cancer. Integral to the discussion are the roles that prebiotics and probiotics play in critical aspects of the GLA. The review aims to bridge the conventional knowledge with recent knowledge of therapeutic agents.MethodsA literature review was performed using the keywords “gut-lung axis,” “prebiotics,” “probiotics,” and “lung cancer” on Google Scholar, PubMed, and JSTOR.ResultsProbiotic bacteria have a positive effect in maintaining beneficial bacteria in the gastrointestinal tract, which subsequently shows significant effects in maintaining lung health. Coupled with the efficacy of probiotics is a diet rich in prebiotics required to maintain a healthy gastrointestinal tract microbiota. Probiotics and prebiotics have specific mechanisms of action to prevent lung health-related diseases such as lung cancer. Recent advances have shown the potential of non-toxic and sustainable therapeutic agents for reversal of dysbiosis in GLA.ConclusionResearch suggests that the gastrointestinal tract microbiota has a crucial role in the onset and prevention of lung cancer. Lung cancer, which is prevalent in almost every country around the globe, is found to be associated with the occurrence of various other co-morbidities. Seeking new methods to maintain lung health and prevent lung diseases, including lung cancer, remains urgent, especially in the post-COVID era.